2021
DOI: 10.31557/apjcp.2021.22.5.1599
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake and Factors Associated with Mastectomy among Chinese Women with Breast Cancer: A Retrospective Observational Study

Abstract: Objective: There are limited data concerning the use of mastectomy and associated factors in China in recent years. This study aimed to investigate the uptake of mastectomy and determine the associations between patients' characteristics and mastectomy among Chinese women with breast cancer. Methods: A retrospective analysis of female breast cancer cases from January 2015 to December 2019 from a tertiary hospital was conducted. Socio-demographic data, clinical data, and surgery types were collected by reviewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Interestingly, younger NC women harbor significant concerns about breast value and femininity, and are therefore more likely to pursue breast reconstruction. Zhang et al 40 reported that 35.3% of patients believed that “breast conservation is not necessary for old people.” 6,15,31,41 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, younger NC women harbor significant concerns about breast value and femininity, and are therefore more likely to pursue breast reconstruction. Zhang et al 40 reported that 35.3% of patients believed that “breast conservation is not necessary for old people.” 6,15,31,41 …”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al 40 reported that 35.3% of patients believed that "breast conservation is not necessary for old people." 6,15,31,41 Marital status and social support were found to be 2 of the main factors that affected the acceptance of reconstruction in one study. 41 In particular, husbands were again some of the most influential players, with 39.6% suggesting that their wives choose a mastectomy.…”
Section: Cultural Factors Influencing Breast Reconstruction In Chinamentioning
confidence: 90%
See 1 more Smart Citation
“…Another quantitative study also identified that older age (≥ 65 years) was one of factors for refusal of mastectomy among male breast cancer patients [ 3 ]. In contrast, women undergoing mastectomy in China were older and more likely to be married and have at least one child [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low reconstruction rates after mastectomy could be associated with various factors, including ethnicity, low socioeconomic status, the unavailability of this surgery, and personal reasons such as fear of additional surgery and implants (Morrow et al., 2014; Restrepo et al., 2019). In addition, although breast‐conserving surgery (BCS) is increasingly recommended for early breast cancer as a more favorable procedure than mastectomy due to its similar survival rates and better cosmetic results (Fisher et al., 2002; Veronesi et al., 2002), a large percentage of women with early breast cancer still undergo a mastectomy in many countries (Liu, Guo, et al., 2021; Sinnadurai et al., 2018). Understanding women's decision‐making experiences regarding mastectomy is thus important to provide support to these women during this process.…”
Section: Introductionmentioning
confidence: 99%